О некоторых терминах, обозначающих персонал хеттского храма - Чернышева, А. З.
Černyševa, A. Z.; About Some Terms Designating Personnel of the Hittite Temple; engl. Résumé S. 253: LÚMEŠ DINGIRLIM, LÚMEŠ ḫilammateš, ENMEŠ UTÚL DINGIRMEŠ.